ON HYBRIDISATION IN CONTEMPORARY SLOVAK PROSE - SOUČKOVÁ, MARTA (Bohemica Olomucensia, 2023)
In my paper, I see hybridisation as the mixing of multiple, often disparate elements. This term is used in literary studies mainly in connection with postmodernism and its other features (intertextuality, fragmentation, eclecticism, etc.). In Slovak post-revolutionary prose, the boundaries between arts, media, types or genres are often crossed, and there is an increasing number of works that oscillate between non-fiction and fiction, biography and fiction, journalism (reportage) and fiction, popular and artistic literature, or between the arts (visual, film and literary arts). In my paper, I will discuss prose published in 2019-2020: Katarína Kucbelová's book Čepiec, Ivana Gibová's comic short story collection Eklektik Bastard, Veronika Šikulová's non-novel Tremolo ostinato, and Nataša Holinová's prose Prípad starej dámy, which each in a different way break the boundaries of genres or artistic literature. In particular, I will be interested in whether the hybridisation in the analysed prose works, i.e. whether an aesthetically effective form emerges through the crossing of practices from different fields.
Keywords: Slovak prose since 2000; hybridisation; functionality